UNIT 3.8 Isolation of Human Melanoma Stem Cells Using ALDH as a Marker. (20th September 2013) - Luo, Yuchun; Nguyen, Nicholas; Fujita, Mayumi
ABSTRACT: This unit describes a protocol for establishing a patient‐derived tumor xenograft model (PDTX model) of human melanoma and isolating human melanoma stem cells from human melanoma specimens using aldehyde dehydrogenase (ALDH) as a marker. One major limitation of analyzing a small fraction of cancer stem cells from patient tumor samples is that substantial quantities of fresh tumor tissues are not available. To overcome this challenge, we have established a PDTX model of human melanoma. In this model, human tumor tissues obtained from melanoma patients are dissected into small pieces and subsequently implanted into immunocompromised mice. The PDTX tumors retain fundamental genotypic and phenotypic features of the original tumors and are suitable for further biological analyses. Using the PDTX model, we have analyzed ALDH‐labeled human melanoma stem cells. This unit will describe how to establish a PDTX model using human tumor samples. We will also describe how to isolate and analyze ALDH‐labeled human melanoma stem cells using this model. Curr. Protoc. Stem Cell Biol . 26:3.8.1‐3.8.10. © 2013 by John Wiley & Sons, Inc.